ANALISIS POTENSI PAJAK SARANG BURUNG WALLET YANG ADA DI KOTA PAREPARE - Jumriani, Jumriani; Bahruddin, Bahruddin (Universitas Muhammadiyah Parepare, 2021)
This research is intended to obtain some evidence, among others, to determine the amount of swallow nest tax in Parepare City. The type of research that will be used is a descriptive quantitative method, then based on data collection techniques using direct surveys and viewing documents/data in the form of recordings and written reports from the Regional Financial Management Agency of Parepare City. The research instrument serves to determine the focus of research, select informants, collect data, assess data quality, analyze data. Technical analysis of the data used in this study is to use the instrument test measuring instruments as follows: 1). The swallow nest tax calculation model uses the calculation method, the volume of swallow nests is multiplied by the general (applicable) price. 2). Swallow nest tax stipulation is obtained from 10% of the income earned, namely the result of sales (multiplication between the volume of swallow nests and the selling price). Based on the results of research and discussions that have been carried out regarding the potential for swiftlet nest taxes in Parepare City, several conclusions can be drawn: 1). The growth of the income tax revenue of the wallet's nesting mother bird Parepare City has increased every year. This is caused by an increase in revenue from swallow’s nesting tax revenue in Parepare City, among others. The government of City of Parepare realized that the mother's business in breeding swallow’s nests is an enterprise that has sufficient revenue potential for this area. 2). Based on the results of the research, it can be found that the swallow’s nest tax has the potential to increase the Locally-generated revenue of the Parepare City so that the Parepare City Government can maximize the potential of Locally-generated revenue income.